Severe Smallness as Predictor of Adverse Perinatal Outcome in Suspected Late Small-for-Gestational-Age Fetuses: Systematic Review and Meta-analysis. Issue 3 (March 2023) - Meler, E.; Martinez-Portilla, R. J.; Caradeux, J.; Mazarico, E.; Gil-Armas, C.; Boada, D.; Martinez, J.; Carrillo, P.; Camacho, M.; Figueras, F.
ABSTRACT: Various adverse perinatal outcomes, such as neonatal morbidity, fetal death, suboptimal neurodevelopment, and delayed effects as an adolescent and adult, are associated with fetal growth restriction (FGR). Failure to detect this condition prenatally is recognized as a contributor to avoidable perinatal death. This systematic review and meta-analysis assessed the evidence regarding the use of severe smallness (eg, birth weight <3%ile) for prediction of adverse perinatal outcome in fetuses with suspected late-onset small for gestational age (SGA) birth. Study eligibility included third-trimester singleton pregnancies with suspected SGA fetuses, based on an estimated fetal weight (EFW) or abdominal circumference <10th percentile, diagnosed at or after 32 weeks' gestation. Included studies were both retrospective cohort studies and randomized controlled trials and reported on the following outcomes: (1) admission to the neonatal intensive care unit (NICU); (2) neonatal acidosis; (3) cesarean delivery for intrapartum fetal compromise; (4) Apgar score <7 at 5 minutes; (5) perinatal death (including stillbirth and neonatal death within 48 hours after birth); and (6) composite adverse perinatal outcome. The analysis identified a total of 6541 articles via database search, and 1 additional study was identified manually. A final review resulted in the inclusion of 12 cohort studies. The studies included 3639 fetuses with suspected late-onset SGA, of which 1246 had severe SGA <3%ile. Significant associations were found between suspected severe SGA and the composite adverse perinatal outcome, with an odds ratio (OR) of 1.97 (95% confidence interval [CI], 1.33–2.92), NICU admission (OR, 2.87; 95% CI, 1.84–4.47), and perinatal death (OR, 4.26; 95% CI, 1.07–16.93). However, the analysis found limited performance of suspected severe SGA to predict perinatal outcomes, with an area under the curve of 60.9% for the composite adverse perinatal outcome. The meta-analysis results indicate that the performance of severe SGA in the study was poorer than that reported for uterine artery Doppler and cerebroplacental ratio. The current analysis found a positive and negative likelihood ratio of 1.53 and 0.76, respectively, for composite adverse perinatal outcome associated with severe smallness. Despite its association with a higher risk of perinatal complications, suspected severe SGA failed to perform as a standalone parameter for the prediction of adverse perinatal outcome.